Pancreatic Lipase Inhibition Activity in Lipid Absorption Using Traditional Plants: A Systematic Review and Meta-Analysis - Hasim Hasim; Eka Nurul Qomaliyah; Frendy Ahmad Afandi; Didah Nur Faridah (Universitas Gadjah Mada, 2023)
Obesity is a complex and multifactorial disease resulting from excessive accumulation of fat. With a significant annual increase, it has become a health concern across the globe in the last decades. To tackle this problem, an exploration of traditional medicinal plants (TMP) functioning as anti-obesity drugs using an ethnopharmacology approach has been carried out. Research on the drug development of obesity treatment was directed at how to inhibit pancreatic lipase as the enzyme accounted for lipid absorption. Using a systematic review and meta-analysis, this current study investigated TMP anti-obesity from the articles published in 6 scientific databases, i.e., Scopus, Science Direct, Proquest, Cengage Library, Ebsco, and Emerald, using particular keywords. The review resulted in 19 articles containing 91 eligible data based on inclusive and exclusive criteria. Meta-analysis extracted data as follows: IC50, number of replications, and standard error, regarding the anti-obesity effects of medicinal plants and orlistat as a positive control. The results showed 8 medicinal plants showing anti-obesity via inhibition of pancreatic lipase, including Solenostemma argel, Garcinia vilersiana, Phyllanthus chamaepeuce, Cassia auriculata, Moringa oleifera, Ficus carica, Ocimum gratissimum, and Adiantum capillus-veneris.